Transcriptomic profiling of lncRNAs and mRNAs in a venous thrombosis mouse model - Risheng Hao; Haobo Li; Xincheng Li; Jixiang Liu; Xiaofan Ji; Hong Zhang; Zhu Zhang; Peiran Yang; Zhenguo Zhai (iScience)
Summary: This study explores the role of lncRNAs and mRNAs in venous thromboembolism (VTE) using an inferior vena cava (IVC) mouse model. RNA sequencing identified differentially expressed lncRNAs and mRNAs between model and control groups. Enrichment analyses revealed significant pathways, including HIF-1α signaling, glycolysis/gluconeogenesis, and platelet activation. A lncRNA-miRNA-mRNA network highlighted key regulatory interactions. Validation using qRT-PCR confirmed the RNA-seq findings. These results provide insights into the molecular mechanisms of VTE and suggest potential biomarkers and therapeutic targets for thrombosis.